Construction of a global knowledge input-output table - Ronald B. Davies; Dieter F. Kogler; Guohao Yang (University College Dublin, UCD School of Economics, 2023)
This paper describes the construction of the Knowledge Input-Output (KIO) table constructed as part of the RETHINK project. Using PATSTAT data on forty years of patent data from across the globae, the KIO table provides information on the number of patent applications across ten major patenting countries and the rest of the world and across 131 technology classifications. It further provides a network of patent citations, thus indicating how patents build from existing knowledge and contribute to the construction of further innovation. In addition to describing the KIO's construction, we provide a number of stylized facts on patenting activity and the citation network. These facts illustrate the lessons that can be learned from patent citation data while also identifying potential pitfalls in their use.
Keywords: O31; O33; R15; 330; Patents; Citations; Input-Output Table; Diffusion; Innovation